(untitled) (Zia e Tahqeeq, 2025)
Ibn al-Farid (d. 632/1334) was a great Egyptian Sufi poet who was known because of his spontaneous flow of spirituality and love that was the dominated feature of his poetry. He had a tremendous impact on the subsequent Sufi thoughts and poetry. The echo of his spiritual poetry can be heard even after centuries by Sultan Bahoo (d. 1102) in his Punjabi and Persian poetry. This paper aims to compare and contrast the ideas of both Sufi poets. Interestingly Ibn Farid is known as Sultan al-Ashiqin while Sultan Bahoo is famous as Sultan al-Arfin and both of them not only attracted the intellectuals but also masses. It is attempted to conduct thematic and comparative study of both poets.